Republicanism, religion, and the soul of America - Sandoz, Ellis (Eric Voegelin Institute series in political philosophy, 2006)
Republicanism and religion: some contextual considerations -- Foundations of American liberty and rule of law -- Education and the American founding -- Americanism: the question of community in politics -- Carrying coals to Newcastle: Voegelin and Christianity -- Medieval rationalism or mystic philosophy? the Strauss-Voegelin debate -- Gnosticism and modernity -- The spirit of Voegelin's late work -- Truth and the experience of epoch in history